Remarks on the Problem of Age Determination in Fetuses and Newborns - Gworys, Bohdan (Anthropological Review, 1988)
The determination of the exact moment of conception is burdened with an error, and; the moment of birth does not indicate to the same degree of development of the newborns. These facts as well as the specificity of the material on which the investigation of fetal growth is based result in numerous methodological problems in research on ontogenesis of the prenatal period.